Edukasi Ekonomi Kreatif Masyarakat Pesisir Menuju Ketahanan Pangan Keluarga Di Masa Pandemi Covid 19 - Yarmaliza Yarmaliza; Teungku Nih Farisni; Fitriani Fitriani; Zakiyuddin Zakiyuddin; Fitrah Reynaldi; Veni Nella Syahputri; Rinaldy Rinaldy (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The very rapid spread of the COVID-19 pandemic outbreak has had an impact on the world economy, including in the food and agriculture sectors. A 1% decline in China's economic growth in 2020 could have an impact of around 0.3% on the existing economy in Indonesia, including in Aceh. Therefore, the creative economic stimulus is one of the most appropriate alternatives in overcoming the economic problems of the community, by utilizing local commodities through the innovation of tempeh powder broth as family food security in Purwodadi Village, Nagan Raya Regency. The purpose of this activity is to provide creative economy education to coastal communities, especially poor families towards family food security during the COVID 19 pandemic. The method of activities used is through 5 approaches, namely coaching, formation, implementation, monitoring, assistance and evaluation. The result of this service is the formation of Micro, Small and Medium Enterprises (MSMEs) in coastal communities, especially in poor families, so that it can be one of the efforts towards family food security during the COVID 19 pandemi.